An integrated overview of bacterial carboxylesterase: structure, function and biocatalytic applications - Mohd Johan, Ummie Umaiera; Raja Abd Rahman, Raja Noor Zaliha; Kamarudin, Nor Hafizah Ahmad; Mohamad Ali, Mohd Shukuri (Elsevier, 2021)
Carboxylesterases (CEs) are members of prominent esterase, and as their name imply, they catalyze the cleavage of ester linkages. By far, a considerable number of novel CEs have been identified to investigate their exquisite physiological and biochemical properties. They are abundant enzymes in nature, widely distributed in relatively broad temperature range and in various sources; both macroorganisms and microorganisms. Given the importance of these enzymes in broad industries, interest in the study of their mechanisms and structural-based engineering are greatly increasing. This review presents the current state of knowledge and understanding about the structure and functions of this ester-metabolizing enzyme, primarily from bacterial sources. In addition, the potential biotechnological applications of bacterial CEs are also encompassed. This review will be useful in understanding the molecular basis and structural protein of bacterial CEs that are significant for the advancement of enzymology field in industries.